Nanoodor Particles Deliver Drugs to Central Nervous System via Olfactory Pathway - Wei Zhang; Xingwang Ji; Qianyanqiu Zhao; Jinyao Qi; Wen Guo; Gaoshuo Zhang; Yujing Guan; Shenglong Li; Yuling Mao (Advanced Science)
Abstract Central nervous system (CNS) disorders confront significant challenges in drug delivery due to the blood–brain barrier (BBB). Inspired by the rapid and precise binding of odor molecules to olfactory receptors (ORs), this research uses thiolated HPMA to construct odor nanoparticles (nanoodors) capable of delivering drugs to the CNS via the olfacto–cerebral pathway to overcome the delivery obstruction. The nanoodor core is used to encapsulate agomelatine (AGO), a CNS‐targeting antidepressant, and the encapsulation efficiency exceeded 80%. A series of thiol‐presenting nanoscale structures with different surface densities of thiol groups are constructed, and the effectiveness positively correlated with the density of thiol groups on their surface. Notably, the nanoodors enable precise brain‐targeted delivery, outperforming commercially available oral formulations in terms of drug accumulation in the brain and antidepressant effects. The study of the nanoodor transport and action mechanisms revealed that after binding to ORs, the nanoodors are rapidly delivered to the brain via the olfactory pathway. Nanoodors, the first design to deliver CNS drugs via the olfactory pathway by mimicking natural smells for the treatment of CNS disorders, are expected to achieve clinical transformation, benefiting human health.